Case report: Recurrent severe mitral regurgitation due to ruptured artificial chords after transapical Neochord mitral valve repair - Zhou, Mi; Un, Ka-chun; Wong, Chun Ka; Wong, On Yat; Siu, David Chung Wah; Yin, Lixue; Chan, Daniel Tai-leung; Lam, Simon Cheung Chi (Frontiers in Cardiovascular Medicine, 2022)
Transapical Neochord mitral valve repair has been proven to be a technically safe procedure to correct primary mitral regurgitation (MR). Recurrent MR due to ruptured artificial chords is rare. Here, we present 2 cases of recurrent severe MR due to the detached or partially ruptured artificial chords after Neochord procedure.